Kunstapotheke: Site-responsive choreographies within the premises of an abandoned pharmacy. Issue 2 (1st December 2019) - Rainer, Lucia
AbstractKunstapotheke is a choreographic project that was based in the premises of an abandoned pharmacy and shopping district in the northern part of Hamburg, Germany. Meandering between disused pharmacy facilities and its urban surroundings, a group of performers and myself explored how urban scores render possible to journey through time. Being interested in how past narratives might craft and shape possible urban futures, we experienced that time often shatters into fragments, evoking the question: How can urban scores respond to and subvert urban narratives and their choreographies? To be able to answer this question we explored the urban surroundings with the following choreographic tools: (1) pre-selection and re-selection, (2) combination, (3) intermedial variation and (4) contextualization and re-contextualization. Working with these choreographic tools revealed that past narratives are inevitably tied to spatiotemporal frameworks, frames and framings, which are unavoidably linked to overall complexes interrelated with autobiographical, cultural, political and economic constellations. Thus, we incessantly found ourselves within spatiotemporal encounters that allowed for different types of temporalities to not only bubble beyond the surface, but effectively irrupt and disrupt one another. In the course of this, different spatial realities unfolded, preoccupying themselves exclusively with individual processes of occurrence. The project Kunstapotheke repeatedly contextualized and re-contextualized these occurrences, defining the choreographic process as a practice of simultaneous reference and transcription.